Design and analysis of high isolated super compact 2 × 2 MIMO antenna for WLAN application. Issue 11 (11th August 2021) - Kaur, Manpreet; Singh, Hari Shankar
Abstract: In this article, a DGS structure is applied to enhance the inter‐port isolation of super compact 2 × 2 MIMO antenna. Each element of MIMO antenna configuration is designed using a planar inverted‐F antenna (PIFA) having dimensions 7 × 7 × 0.8 mm 3 and elevated at 2.8 mm from the ground plane of dimensions 100 × 50 × 0.8 mm 3 (comparable to the size of mobile handsets). The proposed antenna operates from 5.2 to 6 GHz resonating at 5.65 GHz which is suitable for WLAN applications. The proposed design with and without the isolation enhancement technique is resonating at 5.65 GHz. Therefore, the proposed DGS structure is acting as a perfect isolator without affecting the reflection coefficient of the MIMO antenna configuration. It provides high isolation enhancement from 12 to 25 dB at the resonance frequency. All the diversity parameters of the MIMO configuration are calculated and found within the desirable limits. Thus, it is found that the proposed antenna is well suited for modern wireless applications (WLAN). The radiation performances such as 2D and 3D patterns, total antenna efficiency, and peak realized gain are calculated and analyzed. Finally, a prototype is fabricated and validated experimentally.